Monte Carlo Reliability Model for Single-Event Transient on Combinational Circuits - Liu, Baojun; Cai, Li (IEEE transactions on nuclear science, 2017)
A Monte Carlo model was proposed to evaluate the reliability for single-event transient (SET) on combinational circuits. The masking effects, including logical, electrical, and timing masking effects, and the randomicity of SET are considered in the proposed model. Based on the reported model, an electrical masking model is also presented to apply for the reliability model. For ISCAS'85 benchmark circuits, the effects of SET duration, the masking effects, and the multi-SETs on the reliability are analyzed by the proposed model. The results are reported showing that the proposed model can be effectively used to analyze the reliability of a complex circuit.